RESULTS OF STAGED ENDOVASCULAR MYOCARDIAL REVASCULARISATION IN PATIENTS TREATED FOR ACUTE CORONARY SYNDROME WITH ST-SEGMENT ELEVATION AND MULTIVESSEL DISEASE - Alexander V. Bocharov; Leonid V. Popov (Кубанский научный медицинский вестник, 2019)
Aim. To evaluate the results of complete functional endovascular myocardial revascularisation which is performed early after stenting the culprit artery (within 90 days) with third-generation sirolimus-eluting stents in patients treated for acute coronary syndrome (ACS) with ST-segment elevation and multivessel disease. Materials and methods. We analysed the results of a 2-year follow-up treatment period of patients suffering from ACS with ST-segment elevation and multivessel disease who had undergone urgent stenting of culprit artery. Within 90 days after stenting, a complete functional endovascular myocardial revascularisation was performed using third-generation sirolimus-eluting stents. The efficacy and safety of the procedure was evaluated according to the non-inferiority criteria in comparison with the literature data on myocardial revascularisation by coronary artery bypass surgery. Results. In the course of follow-up treatment, 1 lethal myocardial infarction (after 18 months from complete revascularisation) and 2 non-lethal myocardial infarctions were registered. The symptoms of angina returned in 7 patients, 6 of whom had undergone unplanned re-revascularisation within 6 to 12 months following complete revascularisation. The MACCE rate was 0.143 [95% confidence interval: 0.0770; 0.2497]. Conclusion. In patients having ACS with ST-segment elevation and multivessel disease, endovascular myocardial revascularisation performed early after stenting the culprit artery is equivalent to coronary artery bypass surgery in terms of cardiovascular mortality rates, as well as incidence of non-fatal cardiovascular events. However, such an approach underperforms compared to coronary artery bypass surgery in terms of a composite endpoint of MACCE and the number of required re-interventions.